The inhibitor of apoptosis (IAP) proteins are critical regulators of signaling pathways and targets for anti-cancer therapy - de Almagro, M.C.; Vucic, D. (Experimental Oncology, 2012)
Cell death regulation is vital for maintenance of homeostasis and proper development of multicellular organisms. Inhibitor of apoptosis (IAP) proteins are implicated in multiple ways in cell death regulation, ranging from inhibition of apoptosis and necrosis to the regulation of cell cycle and inflammation. Due to their prominent ability to control cell death and elevated expression in a variety of cancer cell types, IAP proteins are attractive targets for the development of novel anti-cancer treatments. The most widely used strategy for targeting IAP proteins is based on mimicking the natural IAP antagonist, SMAC/DIABLO. IAP antagonists are currently being tested in humans and they were designed for anti-cancer therapy but they could potentially also be considered for treatments of the immune system disorders. In this manuscript we will review the functional roles of IAP proteins, specifically of c-IAP1, c-IAP2, ML-IAP and XIAP, and evaluate IAP targeting strategies for disease treatments. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.